Sleeping Beauty and the Microenvironment Enchantment: Microenvironmental Regulation of the Proliferation-Quiescence Decision in Normal Tissues and in Cancer Development - Fiore, Ana Paula Zen Petisco; Ribeiro, Pedro de Freitas; Bruni-Cardoso, Alexandre (Frontiers in Cell and Developmental Biology, 2018)
Cells from prokaryota to the more complex metazoans cease proliferating at some point in their lives and enter a reversible, proliferative-dormant state termed quiescence. The appearance of quiescence in the course of evolution was essential to the acquisition of multicellular specialization and compartmentalization, and is also a central aspect of tissue function and homeostasis. But what makes a cell cease proliferating even in the presence of nutrients, growth factors and mitogens? And what makes some cells “wake up” when they should not, as is the case in cancer? Here, we summarize and discuss evidence showing how microenvironmental cues such, as those originating from metabolism, extracellular matrix (ECM) composition and arrangement, neighboring cells and tissue architecture, control the cellular proliferation-quiescence decision and how this complex regulation is corrupted in cancer.